Does enterprise risk management bolster investor confidence? Evidence from options‐based restatement contagion, investment, and misstatements - Neel, Michael; Xu, Jianren (Contemporary Accounting Research, 2025)
Using industry restatement contagion as an external negative shock, we study the effectiveness of enterprise risk management (ERM) in mitigating downside risk and enhancing investor confidence. We find that ERM curbs overinvestment and earnings misstatement among firms when other firms in their industry engage in undisclosed misstatements that are subsequently restated. Following the announcements of these industry restatements, peers with ERM experience a smaller increase in implied volatility skewness. These effects are driven by peers with young CEOs, complex segment structures, low prior earnings performance, and in competitive industries. Overall, our findings highlight ERM's role in bolstering investor confidence by effectively managing firms' underlying risks.